Teaching and learning Islam in International Islamic University Malaysia (IIUM): some aspects of relevantization of Islamic sciences - Zein, Ibrahim Mohamed (Revelation and Science, IIUM, 2014)
This article focuses on the experiment of teaching and learning Islam in the International Islamic University Malaysia (IIUM). Although it devoted a considerable space for the Kulliyyah of Islamic Revealed Knowledge and Human Sciences (KIRKHS), yet the experiences of other Kulliyyahs were not completely ignored. It argued that the new ijtihad in teaching and learning Islam, which has been developed in KIRKHS has its impact on other Kulliyyahs. In this regard, the most significant feature has to do with both the definition of the religious phenomenon and the unit of analysis within which it has been evaluated. Obviously this methodic approach has a remarkable effect on the discipline of History of Religions. Because of this new orientation in the study of this discipline, one can say that IIUM’s experiment in teaching and learning religion in general and Islam in particular is refreshingly different. More to the point, it changed significantly the way in which religious phenomenon has been approached in a university set-up